Pengaruh Model Pembelajaran Learning Cycle 5E Terhadap Kemampuan Menjelaskan Energi Alternatif Siswa Kelas IV SDN Mojoroto 4 Kota Kediri - Aprilia Aksari; Frans Aditia Wiguna; Muhamad Basori (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
The purpose of this research is to perceive the increasing effect of the ability to explain an alternative energy sources using a learning model called '5E Learning Cycle. This research uses a quantitative approach in using the experimental method with the research design refers to non-randomized pretest-posttest control group design. The data collection instrument is using tests and data analysis techniques with the normality test, homogeneity and hypothesis testing (using the t-test). Based on the analysis results, the use of the learning model of '5E Learning Cycle' has some effects on the ability to explain alternative energy. From the analysis results that has been done, it is proven that; (1) The use of the learning model of '5E Learning Cycle' has a significant effect on the ability of the 4th Graders in SD Negeri Mojoroto 4 Kota Kediri to explain alternative energy with 85.07% of the classical completeness. (2) The use of the conventional learning model has no significant effect on the ability of the 4th graders in SD Negeri Mojoroto 4 Kota Kediri to explain alternative energy with 54,9% of the classical completeness. (3) There are some highly significant differences in the use of the learning model of '5E Learning Cycle' and the conventional learning model on the ability to explain alternative energy which the use of the '5E Learning Cycle' has its prime on this analysis results. The conclusion of this research has perceived that there are some highly significant differences of '5E Learning Cycle' and the conventional learning model in improving students' ability to explain the science content of alternative energy material.